Russia in the Perspective of Historical Sociology: Heuristic Perspectives and Methodological Problems - T. A. Dmitriev; O. V. Kildyushov (Социология власти)
The article discusses the heuristic and methodological potential of historical sociology as one of the most dynamically developing disciplines of modern social and scientific knowledge. It is argued that this area of research is functionally capable of taking on the role of today's analytical philosophy of history in the form of integrity and, at the same time, the operational reflection of the historical experience of our country. The article points out the deficient nature of previous conceptualizations of the domestic past from the point of view of historical sociology. First, the development of this discipline in the West is briefly analyzed, starting with the classics of world sociology. The qualitative and quantitative growth of historical and sociological research in the second half of the 20th century—which led to a significant expansion of the explanatory repertoire of macrosociology—is highlighted. Next, the ambivalent position of historical sociology in Russia is discussed, where—despite the existing interest in its methodological categories and substantive results—a full-fledged institutionalization of this sociological discipline has not yet occurred. Thus, a conclusion is made about the existence of a serious local tradition of interest in historical-sociological synthesis, starting with the classics of historiography and pioneers of Russian sociology at the turn of the 19th and 20th centuries. At the same time, substantial progress is highlighted on the part of the domestic social-scientific community in the reception of the achievements of world-historical sociology at the beginning of the 21st century. The next section shows the particular relevance of modern historical-sociological approaches to the problematization of the past in the context of the domestic epistemological situation. A number of the most promising thematic complexes in modern Russian academia are highlighted. In conclusion, we highlight issues concerning framework research and scientific organization faced by historical sociology in Russia.